Psychodidactic approach in the development of language competences in university students within blended learning. (4th May 2018) - Cerna, Miloslava
Abstract: The paper discusses the deployment of cognitive and affective components for teaching languages in a blended learning university setting. A modified expectancy model of motivation was designed and applied. The usability testing of a language education website was used as a framework with affective and cognitive features. The selection of the education website was based on findings gained from the language needs analysis. The level of students' language competence representing the cognitive component was diagnosed based on their results in the placement tests in the DIALANG language website. Many students showed progress in language knowledge by the end of the semester. Results were higher than students had expected and enough to encourage further research. The affective part is discussed in the modified expectancy model of motivation that was designed and applied. The psychodidactic approach used in the research met students' motivational and emotional needs without sacrificing their improved competence in language development.